The founding of institutional economics : the leisure class and sovereignty (Routledge studies in the history of economics., 2002)
Institutional economics has been a major part of economic thought for the whole of the twentieth century, and today remains crucial to an understanding of the development of heterodox economics. The two principal publications that founded the school were Veblen's The Theory of the Leisure Class and Commons's A Sociological View of Sovereignty, both published in 1899. As a tribute to these two seminal works, Warren Samuels has assembled an exceptionally prestigious international group of scholars to produce this landmark volume celebrating the centenary. The chapters asses.